The INT6 cancer gene and MEK signaling pathways converge during zebrafish development. - Michal Grzmil; Danny Whiting; John Maule; Corina Anastasaki; James F Amatruda; Robert N Kelsh; Chris J Norbury; E Elizabeth Patton (PLoS ONE)
Background Int-6 (integration site 6) was identified as an oncogene in a screen of tumorigenic mouse mammary tumor virus (MMTV) insertions. INT6 expression is altered in human cancers, but the precise role of disrupted INT6 in tumorigenesis remains unclear, and an animal model to study Int-6 physiological function has been lacking. Principal findings Here, we create an in vivo model of Int6 function in zebrafish, and through genetic and chemical-genetic approaches implicate Int6 as a tissue-specific modulator of MEK-ERK signaling. We find that Int6 is required for normal expression of MEK1 protein in human cells, and for Erk signaling in zebrafish embryos. Loss of either Int6 or Mek signaling causes defects in craniofacial development, and Int6 and Erk-signaling have overlapping domains of tissue expression. Significance Our results provide new insight into the physiological role of vertebrate Int6, and have implications for the treatment of human tumors displaying altered INT6 expression.